Photovoltaic support mortar composite steel pipe and manufacturing process thereof

CN123003207APending Publication Date: 2026-10-30JIANGSU OCEAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610912029.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

同时,开口薄壁型钢存在抗扭刚度差的致命缺陷,多项光伏支架的破坏案例也证实了这一点

Benefits of technology

1.显著提升光伏支架承重构件的结构性能:通过硅灰-玄武岩纤维协同改性陶砂砂浆与薄壁钢管的复合,实现二者协同受力,充分发挥钢管的抗拉性能和改性砂浆的抗压、抗裂性能。填充砂浆后,薄壁钢管的局部屈曲得到有效约束,复合钢管的抗压、抗弯、抗扭刚度及承载能力均获得大幅提升,在风振作用下应力幅明显减小。砂浆与钢管复合后,复合材料的阻尼系数较纯钢结构大幅提高,振动衰减速度显著增加,疲劳寿命显著延长。上述性能提升有效解决了现有纯薄壁型钢承载性能不足、刚度偏低、在风荷载反复作用下易疲劳开裂及失稳破坏的核心问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003207A_ABST
    Figure CN123003207A_ABST
Patent Text Reader

Abstract

The application discloses a kind of mortar composite steel pipes for photovoltaic support and its manufacturing process, it is related to support steel pipe technical field, existing photovoltaic support thin-walled steel pipe bearing capacity, rigidity and fatigue performance are insufficient, long-term service is easy to deform, cracking and instability damage, and filling material and steel pipe poor adaptability.The composite steel pipe of the application includes thin-walled steel pipe body and modified ceramic sand mortar poured in its inside, modified ceramic sand mortar is composed of cement, fly ash, silica fume, graded ceramic sand, basalt fiber, micro-expansion agent, water reducing agent, redispersible latex powder, water-retaining thickener, modified nano magnesium oxide, defoaming agent and water in specific ratio.Forming process includes thin-walled steel pipe pretreatment, modified ceramic sand mortar preparation, mortar pouring and curing molding.Through the synergistic effect of water-retaining thickener, modified nano magnesium oxide and defoaming agent, mortar has high fluidity, high bonding strength and high filling density, and the bearing capacity and rigidity of composite steel pipe are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of support steel pipe technology, specifically, it relates to a mortar composite steel pipe for photovoltaic supports and its manufacturing process. Background Technology

[0002] Photovoltaic support structures are the core load-bearing structures of photovoltaic power plants, primarily used to support photovoltaic modules. They must withstand the weight of the photovoltaic modules, wind loads, snow loads, and other forces over long periods, and are mostly used in outdoor environments. This places stringent requirements on the structure's load-bearing capacity, stiffness, fatigue performance, and durability. Currently, the load-bearing components of photovoltaic support structures are mostly made of thin-walled steel, which has the advantages of light weight, convenient installation, and low cost, and is widely used in photovoltaic projects.

[0003] However, existing thin-walled steel structures used in photovoltaic brackets still face many technical challenges in practical applications: First, there are insufficient load-bearing capacity and stiffness. Thin-walled steel has a relatively thin wall thickness (typically 2.0–5.0 mm) and low cross-sectional stiffness. In photovoltaic support structures, purlins constitute the largest proportion of steel used, and cold-formed thin-walled steel is often used as purlin components. However, as the strength of steel increases, the purlin steel becomes increasingly thinner, significantly reducing its stable load-bearing capacity. Under pressure and torque, thin-walled steel pipes are prone to bending, torsion, and deformation, even triggering local instability and leading to overall component instability. Furthermore, open-ended thin-walled steel has a fatal flaw: poor torsional stiffness, as evidenced by numerous photovoltaic support failure cases.

[0004] Secondly, its fatigue performance is poor. The stress on photovoltaic (PV) support structures is primarily controlled by wind loads, resulting in significant wind-induced vibration. Under wind loads, the structure vibrates violently, and thin-walled steel is prone to fatigue cracking under long-term repeated loading, shortening its service life. Studies have shown that the probability of strength failure in PV support purlins is significantly higher than that of stiffness failure; in engineering practice, there are numerous cases of failure due to improper wind load values ​​leading to out-of-plane instability and large deformation of the main purlins.

[0005] Third, the compatibility between steel pipes and filling materials is poor. Existing technologies have attempted to improve component performance by filling steel pipes with concrete or mortar, such as using steel-concrete composite structures for the lower columns, reducing steel usage by decreasing the steel pipe wall thickness. However, existing filling materials generally suffer from the following problems: ordinary concrete or mortar lacks fluidity, making it difficult to fully fill the narrow cavity of thin-walled steel pipes; the bond strength with the inner wall of the steel pipe is low, easily leading to interface delamination; ordinary mortar has an excessively high density (usually >2000 kg / m³), significantly increasing the component's self-weight after filling, making it unsuitable for the lightweight requirements of photovoltaic supports; and its crack resistance and fatigue performance are insufficient, failing to achieve true synergistic stress distribution with the steel pipe. Existing research indicates that while filling steel pipes with lightweight materials such as aerated concrete can reduce self-weight, their strength is relatively low, and the interfacial bonding performance with the steel pipe needs improvement.

[0006] Fourth, performance and cost are difficult to balance. Simply increasing the wall thickness of the steel pipe to improve strength and rigidity will lead to a significant increase in steel consumption, driving up the cost of the support structure. Although composite material supports have advantages such as being lightweight, high-strength, and corrosion-resistant, their elastic modulus is only 15% to 22% of that of galvanized steel, resulting in lower rigidity, and difficulties in joint treatment and higher costs.

[0007] Therefore, there is an urgent need to develop a filler material and its composite steel pipe that combine lightweight, high strength, high rigidity, excellent fatigue performance and high bonding strength, so as to solve the above-mentioned technical problems without significantly increasing costs.

[0008] Therefore, in order to solve the above problems, the present invention provides a mortar composite steel pipe for photovoltaic brackets and its manufacturing process. Summary of the Invention

[0009] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a mortar composite steel pipe for photovoltaic brackets and its manufacturing process.

[0010] The objective of this invention can be achieved through the following technical solutions: A mortar-coated steel pipe for photovoltaic brackets includes a steel pipe and a silica fume-basalt fiber synergistic modified ceramic sand mortar injected inside the steel pipe. The silica fume-basalt fiber synergistic modified ceramic sand mortar, by weight, comprises the following components: 200-400 parts cement; 50-150 parts fly ash; 20-60 parts silica fume; 500-800 parts of graded ceramic sand; 2-10 parts of 6mm short-cut basalt fiber; 5-15 parts of micro-expansion agent; 5-15 parts of high-efficiency water-reducing agent; 5-20 parts of redispersible latex powder; 0.05-0.5 parts of water-retaining thickener; 0.2-1.0 parts of modified nano-magnesium oxide; Defoamer 0.05-0.5 parts; 150-300 parts water; The modified ceramic sand mortar has a water-cement ratio of 0.62-0.96, a wet density of 1200-1500 kg / m³, a flowability of ≥200 mm, and a bond strength to the inner wall of the steel pipe of ≥1.2 MPa.

[0011] As a preferred embodiment of the present invention, the silica fume-basalt fiber synergistic modified ceramic sand mortar comprises the following components by weight: 250-350 parts cement; 80-120 parts fly ash; 30-50 parts silica fume; Graded ceramic sand 600-750 parts; 4-8 parts of 6mm short-cut basalt fiber; 8-12 parts of micro-expansion agent; 8-12 parts of high-efficiency water-reducing agent; 10-15 parts of redispersible latex powder; 0.08-0.3 parts of water-retaining thickener; 0.3-0.7 parts of modified nano-magnesium oxide; Defoamer 0.08-0.3 parts; 180-250 parts water.

[0012] As a preferred embodiment of the present invention, the water-retaining thickener is at least one of styrax, hydroxypropyl methylcellulose ether, or starch ether, and the viscosity of the water-retaining thickener is ≥10000 mPa·s; the outer diameter of the modified nano magnesium oxide is 10-50 nm; and the defoamer is an organosilicon defoamer or a polyether defoamer.

[0013] As a preferred embodiment of the present invention, the redispersible latex powder is an ethylene-vinyl acetate copolymer latex powder with a solid content ≥98%, a minimum film-forming temperature ≤5℃, and a glass transition temperature of -5-10℃; the silica fume-basalt fiber synergistic modified ceramic sand mortar has a 28-day compressive strength of 10-20MPa, a flexural strength ≥4.5MPa, and a bonding strength with steel pipe ≥1.6MPa.

[0014] As a preferred embodiment of the present invention, the graded ceramic sand is a continuous gradation of 0.0-2.5mm, with a bulk density of 700-900kg / m³, a compressive strength ≥1.5MPa, a water absorption rate ≤10%, and a moisture content ≤3%; the silica fume has a SiO2 content ≥90%, a specific surface area ≥15000m² / kg, and a water requirement ratio ≤115%; the 6mm short-cut basalt fibers have a tensile strength ≥3000MPa and an elastic modulus ≥80GPa; the micro-expansion agent has a restricted expansion rate of ≥0.02% at 7d and ≤0.10% at 28d; and the high-efficiency water-reducing agent is a retarded polycarboxylate water-reducing agent with a water reduction rate ≥20%.

[0015] As a preferred embodiment of the present invention, the steel pipe is made of Q235 or Q355 steel with a yield strength ≥235MPa, a wall thickness of 2.0-5.0mm, an outer diameter of 30-150mm, and a length of 1.0-5.0m; the surface of the steel pipe is provided with a hot-dip galvanized layer with a galvanized layer thickness ≥85μm.

[0016] As a preferred embodiment of the present invention, the steel pipe is a round or square pipe; both ends of the steel pipe are provided with sealing plugs, the sealing plugs are made of steel of the same material as the steel pipe, and the thickness is the same as the wall thickness of the steel pipe; one end of the steel pipe is provided with a grouting hole of 15-25mm, and the other end is provided with a venting hole of 5-8mm in diameter; the silica fume-basalt fiber synergistic modified ceramic sand mortar is tightly bonded to the inner wall of the steel pipe, without gaps, honeycomb, or voids.

[0017] As a preferred embodiment of the present invention, the composite steel pipe has a 40%-60% higher axial compressive strength than the pure thin-walled steel pipe, a 20%-30% higher bending stiffness than the pure thin-walled steel pipe, a 40%-60% higher bending load capacity than the pure thin-walled steel pipe, and a 40%-60% higher axial compressive stiffness than the pure thin-walled steel pipe.

[0018] A manufacturing process for mortar-composite steel pipes used in photovoltaic brackets includes the following steps: S1. Steel pipe pretreatment: Select Q235 or Q355 thin-walled steel pipes, remove rust, oil and impurities from the inner wall of the steel pipe, and use sandblasting to make the inner wall roughness reach Sa2.5 level; hot-dip galvanize the surface of the steel pipe, with a zinc layer thickness ≥85μm; weld and connect multiple steel pipes, with the total length controlled at 50-100 meters; weld sealing plugs at both ends of the steel pipe, and set a grouting hole at one end and an exhaust hole at the other end; S2. Preparation of silica fume-basalt fiber synergistic modified ceramic sand mortar: Weigh each component according to the proportion, dry the graded ceramic sand to a moisture content ≤3%, dissolve the high-efficiency water-reducing agent in all water to prepare an aqueous solution for later use; dry mix cement, fly ash, silica fume, micro-expansion agent, redispersible latex powder, water-retaining thickener, modified nano magnesium oxide, and defoamer evenly, then add the graded ceramic sand and 6mm short-cut basalt fiber and continue dry mixing to ensure that the fiber does not agglomerate; add the aqueous solution and wet mix for 2-3 minutes, let stand for 30 seconds and then test the flowability and bulk density until the design requirements are met; S3. Mortar injection: The silica fume-basalt fiber co-modified ceramic sand mortar prepared in S2 is injected into the pretreated thin-walled steel pipe by low-pressure pumping. It is slowly injected from the injection hole, and the air in the pipe is discharged by the vent hole. The injection is stopped when the mortar overflows from the vent hole and no more air bubbles emerge. The vent hole is then sealed. S4. Curing and Shaping: After the cast composite steel pipe has been cured to 50% of its design strength, it is cut according to the design requirements and the ends of the steel pipe are ground and trimmed; curing continues until the design strength is reached, and the production is completed after passing the test.

[0019] As a preferred technical solution of the present invention, in S3, the low-pressure pumping pressure is controlled at 0.2-0.5MPa, the grouting speed is 0.5-1.0m³ / h, and the venting situation of the venting hole is observed in real time during the grouting process. If mortar segregation or clumping occurs, the grouting is stopped immediately, the mortar is re-stirred, and then it is continued. In S4, the composite steel pipe is protected from collision and vibration during the curing process. After the curing is completed, the bonding strength, bending stiffness and load-bearing capacity of the composite steel pipe are tested. After passing the test, it is used for photovoltaic bracket assembly.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. Significantly Improved Structural Performance of Photovoltaic Support Components: By combining silica fume-basalt fiber synergistically modified ceramic sand mortar with thin-walled steel pipes, the two components work synergistically to fully utilize the tensile strength of the steel pipe and the compressive and crack resistance of the modified mortar. After filling with mortar, the local buckling of the thin-walled steel pipe is effectively restrained, and the compressive, bending, and torsional stiffness and load-bearing capacity of the composite steel pipe are significantly improved, with a marked reduction in stress amplitude under wind vibration. After the mortar and steel pipe are combined, the damping coefficient of the composite material is significantly higher than that of the pure steel structure, the vibration decay rate is significantly increased, and the fatigue life is significantly extended. The above performance improvements effectively solve the core problems of insufficient load-bearing capacity, low stiffness, and susceptibility to fatigue cracking and instability failure under repeated wind loads in existing pure thin-walled steel structures.

[0021] 2. Balancing Lightweight and High Performance: Modified ceramic sand mortar uses lightweight ceramic sand as aggregate, resulting in a lightweight texture. When combined with thin-walled steel pipes, thinner-walled steel pipes can be selected under the same load-bearing capacity conditions. This helps control the self-weight of the components, reduce the amount of steel used, and does not increase the load-bearing pressure on the support foundation. It achieves high load-bearing performance of composite steel pipes while also meeting the lightweight requirements. This solves the problem of increased cost caused by increasing wall thickness to improve strength in existing technologies, as well as the problem of excessive self-weight of components caused by using ordinary mortar filling.

[0022] 3. Excellent adhesion and reliable interfacial bonding: Modified ceramic sand mortar uses redispersible latex powder to form a polymer film at the interface to enhance adhesion. A micro-expansion agent compensates for mortar shrinkage to ensure long-term tight adhesion. A water-retaining thickener improves the mortar's cohesiveness and water retention to prevent segregation during grouting. Modified nano-magnesium oxide fills micropores to enhance interfacial density. An antifoaming agent eliminates air bubbles introduced during grouting to avoid interfacial defects. The synergistic effect of these components enables the modified mortar to form a reliable interfacial bond with the inner wall of the steel pipe, effectively preventing interfacial peeling and voids during long-term service. This solves the technical problems of poor compatibility between existing filler materials and steel pipes, and easy interfacial peeling, ensuring the long-term synergistic stress resistance of the composite steel pipe.

[0023] 4. Excellent grouting performance and reliable filling quality: Modified ceramic sand mortar has good fluidity. Combined with the anti-segregation effect of water-retaining thickener and the defoaming effect of defoamer, it can be smoothly poured into the narrow inner cavity of thin-walled steel pipes using a low-pressure pump. It can self-level and self-compact without vibration, ensuring that the mortar fully fills the inside of the steel pipe. After grouting, there are no voids, honeycombs, or air bubbles trapped inside the steel pipe. The filling quality is stable and reliable, greatly reducing performance dispersion and quality risks caused by incomplete filling. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a schematic diagram of the composite steel pipe of the present invention; Figure 2 This is a comparison curve of the compressive strength of the composite steel pipe and the pure thin-walled steel pipe of the present invention; Figure 3 This is a process flow diagram of the present invention. Detailed Implementation

[0026] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention: Example 1

[0027] This embodiment provides a mortar composite steel pipe for photovoltaic brackets, the structure of which is as follows: Figure 1 As shown, the structure includes a steel pipe and silica fume-basalt fiber synergistic modified ceramic sand mortar injected inside the steel pipe. The steel pipe is made of Q355 steel with a yield strength of 355MPa, a wall thickness of 2.0mm, an outer diameter of 70mm, and a length of 2.0m. The surface of the steel pipe is coated with a hot-dip galvanized layer with a thickness of 85μm. The steel pipe is circular, with sealing plugs at both ends. The sealing plugs are made of the same steel as the steel pipe and have the same thickness as the steel pipe wall. One end of the steel pipe has a 20mm grouting hole, and the other end has a 6mm diameter vent hole.

[0028] The silica fume-basalt fiber synergistic modified ceramic sand mortar, by weight, consists of the following components: 280 parts of P·O 42.5 cement; 100 parts of fly ash; 40 parts of silica fume; 680 parts of graded ceramic sand; 6 parts of 6mm short-cut basalt fiber; 10 parts of micro-expansion agent; 10 parts of high-efficiency water-reducing agent; 12 parts of redispersible latex powder; 0.15 parts of water-retaining thickener; 0.5 parts of modified nano-magnesium oxide; 0.15 parts of defoamer; and 215 parts of water. The graded ceramic sand is a continuous gradation of 0.0-2.5mm, with a bulk density of 800kg / m³, a compressive strength of 1.8MPa, a water absorption rate of 8%, and a moisture content of 1.5%. The silica fume has a SiO2 content of 92%, a specific surface area of ​​16000m² / kg, and a water requirement ratio of 110%. The 6mm short-cut basalt fiber has a tensile strength of 3200MPa and an elastic modulus of 85GPa. The limited expansion rate of the micro-expansion agent is 0.025% at 7 days and 0 at 28 days. 0.8%; the high-efficiency water-reducing agent is a retarded polycarboxylate water-reducing agent with a water reduction rate of 25%; the redispersible latex powder is ethylene-vinyl acetate copolymer latex powder with a solid content of 98.5%, a minimum film-forming temperature of 3℃, and a glass transition temperature of 0℃; the water-retaining thickener is hydroxypropyl methylcellulose ether with a viscosity of 15000 mPa·s (2% aqueous solution, 20℃); the modified nano-magnesium oxide has an outer diameter of 30 nm and is surface-modified with a silane coupling agent for hydrophobicity; the defoamer is an organosilicon defoamer. The water-cement ratio of the modified ceramic sand mortar is 0.79, and the wet bulk density is 1350 kg / m³.

[0029] like Figure 3 As shown, the manufacturing process of the mortar composite steel pipe for the photovoltaic support is as follows: Step 1: Steel Pipe Pretreatment. Select qualified Q355 thin-walled steel pipes and use sandblasting equipment to remove rust, oil, and impurities from the inner wall of the pipes, achieving an inner wall roughness of Sa2.5. The inner wall of the sandblasted pipes should be grouted with mortar within 24 hours. Hot-dip galvanize the steel pipe surface, ensuring a zinc coating thickness ≥85μm. After passing inspection, cool to room temperature. Weld multiple steel pipes together, with a total length controlled to 80 meters to improve mortar grouting efficiency. Secure sealing plugs at both ends of the steel pipes by welding, ensuring no missed welds or incomplete welds during the welding process. Apply anti-corrosion treatment to the weld joints and install a grouting hole at one end and an vent hole at the other.

[0030] Step 2: Preparation of silica fume-basalt fiber co-modified ceramic sand mortar. Weigh each component according to the proportion. Place the graded ceramic sand in a drying equipment at 90℃ and dry for 2.5 hours until the moisture content is ≤3%. After drying, remove impurities and lumps from the ceramic sand. Dissolve the high-efficiency water-reducing agent in all water and stir evenly to prepare an aqueous solution for later use. Place P·O 42.5 cement, fly ash, silica fume, micro-expansion agent, redispersible latex powder, water-retaining thickener, modified nano magnesium oxide, and defoamer into a small forced mixer. Adjust the mixer speed and dry mix for 1 minute to ensure that the cementitious materials are mixed evenly. Then add the pretreated graded ceramic sand and 6mm short-cut basalt fibers, and continue to dry mix for 1 minute to ensure that the ceramic sand and fibers are evenly dispersed in the cementitious materials without fiber agglomeration. Slowly add the above-prepared aqueous solution to the mixer while stirring for 2.5 minutes until the mortar is uniform, fine, free of lumps and segregation, and in a self-flowing state. After mixing, let it stand for 30 seconds and observe the mortar state. Use a flowability test bench to test the mortar flowability and use the volumetric method to test the mortar density, and adjust it to meet the design requirements.

[0031] Step 3: Mortar Injection. The silica fume-basalt fiber co-modified ceramic sand mortar prepared in Step 2 is injected into the pretreated thin-walled steel pipe using a low-pressure pump. Before injection, the thin-walled steel pipe is placed horizontally, ensuring the vent holes face upwards. During injection, the mortar is slowly injected through the grouting holes of the steel pipe, using the vent holes to expel air from the pipe. The injection speed is controlled at 0.8 m³ / h, and the low-pressure pump pressure is controlled at 0.35 MPa to avoid excessively fast injection speeds that could lead to air retention. During the injection process, the venting status of the vent holes is observed in real time. When mortar overflows from the vent holes and no more air bubbles emerge, injection is stopped, and the vent holes are immediately sealed with sealing plugs to prevent mortar overflow and air entry, ensuring a dense mortar filling. After injection, the surface of the steel pipe is cleaned to remove any overflowing mortar.

[0032] Step 4: Curing and Shaping. The poured composite steel pipe is cured under natural conditions, avoiding collisions and vibrations to prevent the mortar from peeling off the inner wall of the pipe. After curing to 50% of the design strength (approximately 7 days), the composite steel pipe is cut according to design requirements, and the ends are ground and trimmed to ensure they meet connection requirements. Curing continues until the design strength is reached in 28 days, completing the fabrication of the composite steel pipe. After curing, the bond strength, bending stiffness, and load-bearing capacity of the composite steel pipe are tested according to the GB / T 50152-2012 standard. Once the tests are passed, it is used for photovoltaic bracket assembly.

[0033] Testing revealed that in the composite steel pipe prepared in this embodiment, the silica fume-basalt fiber synergistic modified ceramic sand mortar adhered tightly to the inner wall of the steel pipe, without gaps, honeycombs, or voids, with a bonding strength of 1.65 MPa. The 28-day compressive strength of the modified ceramic sand mortar was 15.6 MPa, and the flexural strength was 5.2 MPa. The axial compressive strength of the composite steel pipe was 132.8 kN, an increase of 54.8% compared to the pure thin-walled steel pipe (85.8 kN); the bending stiffness was increased by 27.4% compared to the pure thin-walled steel pipe; the bending load capacity was increased by 58.2% compared to the pure thin-walled steel pipe; and the axial compressive stiffness was increased by 58.3% compared to the pure thin-walled steel pipe. Example 2

[0034] The difference between this embodiment and Embodiment 1 is that the steel pipe is made of Q235 steel with a yield strength of 245MPa, a wall thickness of 3.0mm, an outer diameter of 100mm, and a length of 3.0m; the steel pipe is a square pipe. The silica fume-basalt fiber synergistic modified ceramic sand mortar, by weight, consists of the following components: 250 parts P·O 42.5 cement; 120 parts fly ash; 30 parts silica fume; 750 parts graded ceramic sand; 4 parts 6mm short-cut basalt fiber; 12 parts micro-expansion agent; 8 parts high-efficiency water-reducing agent; 15 parts redispersible latex powder; 0.08 parts water-retaining thickener; 0.7 parts modified nano-magnesium oxide; 0.08 parts defoamer; and 250 parts water. The water-retaining thickener is a warm-rolled adhesive with a viscosity of 12000 mPa·s (2% aqueous solution, 20℃); the modified nano-magnesium oxide has an outer diameter of 20 nm; and the defoamer is a polyether defoamer. The water-cement ratio of the silica fume-basalt fiber synergistic modified ceramic sand mortar is 0.96, and the wet bulk density is 1500 kg / m³. The manufacturing process is the same as in Example 1.

[0035] Testing revealed that in the composite steel pipe prepared in this embodiment, the silica fume-basalt fiber synergistic modified ceramic sand mortar adhered tightly to the inner wall of the steel pipe, without gaps, honeycombs, or voids, with a bonding strength of 1.62 MPa. The 28-day compressive strength of the silica fume-basalt fiber synergistic modified ceramic sand mortar was 12.3 MPa, and the flexural strength was 4.6 MPa. The axial compressive strength of the composite steel pipe was increased by 48.5% compared to the pure thin-walled steel pipe, its bending stiffness was increased by 24.6%, its bending load capacity was increased by 51.3%, and its axial compressive stiffness was increased by 49.7%. Example 3

[0036] The difference between this embodiment and Embodiment 1 is that the steel pipe is made of Q355 steel, with a wall thickness of 4.0 mm, an outer diameter of 50 mm, and a length of 1.5 m. The silica fume-basalt fiber synergistic modified ceramic sand mortar, by weight, consists of the following components: 350 parts P·O 42.5 cement; 80 parts fly ash; 50 parts silica fume; 600 parts graded ceramic sand; 8 parts 6 mm short-cut basalt fiber; 8 parts micro-expansion agent; 12 parts high-efficiency water-reducing agent; 10 parts redispersible latex powder; 0.3 parts water-retaining thickener; 0.3 parts modified nano-magnesium oxide; 0.3 parts defoamer; and 180 parts water. The water-retaining thickener is starch ether with a viscosity of 10000 mPa·s (2% aqueous solution, 20℃); the modified nano-magnesium oxide has an outer diameter of 50 nm; and the defoamer is an organosilicon defoamer. The water-cement ratio of the silica fume-basalt fiber synergistic modified ceramic sand mortar is 0.62, and the wet bulk density is 1200 kg / m³. The manufacturing process is the same as in Example 1.

[0037] Testing revealed that in the composite steel pipe prepared in this embodiment, the silica fume-basalt fiber synergistic modified ceramic sand mortar adhered tightly to the inner wall of the steel pipe, without gaps, honeycombs, or voids, with a bonding strength of 1.72 MPa. The 28-day compressive strength of the silica fume-basalt fiber synergistic modified ceramic sand mortar was 19.2 MPa, and the flexural strength was 5.8 MPa. The axial compressive strength of the composite steel pipe was increased by 57.3% compared to the pure thin-walled steel pipe, its bending stiffness was increased by 29.1%, its bending load capacity was increased by 59.8%, and its axial compressive stiffness was increased by 56.9%.

[0038] Comparative Example 1 This comparative example provides a mortar-composite steel pipe for photovoltaic brackets. The difference from Example 1 is that the silica fume-basalt fiber synergistic modified ceramic sand mortar does not contain water-retaining thickeners, modified nano-magnesium oxide, or defoamers; the remaining components and proportions are the same as in Example 1. The manufacturing process is the same as in Example 1.

[0039] Testing revealed that the bond strength between the silica fume-basalt fiber synergistic modified ceramic sand mortar and the inner wall of the composite steel pipe prepared in this comparative example was 1.25 MPa; the 28-day compressive strength of the silica fume-basalt fiber synergistic modified ceramic sand mortar was 14.2 MPa, and the flexural strength was 3.8 MPa. The axial compressive strength of the composite steel pipe was 42.6% higher than that of the pure thin-walled steel pipe, its bending stiffness was 19.8% higher, its bending load capacity was 43.5% higher, and its axial compressive stiffness was 44.1% higher. During the grouting process, slightly poor mortar fluidity was observed, and a small number of air bubbles escaped from the vent holes. Inspection after cutting revealed a small number of tiny honeycomb defects inside the steel pipe.

[0040] Comparative Example 2 This comparative example provides a mortar composite steel pipe for photovoltaic brackets. The difference from Example 1 is that the silica fume-basalt fiber synergistic modified ceramic sand mortar does not contain modified nano magnesium oxide and defoamer, but it does contain a water-retaining thickener (0.15 parts). The remaining components and proportions are the same as in Example 1. The manufacturing process is the same as in Example 1.

[0041] Testing revealed that the bond strength between the silica fume-basalt fiber synergistic modified ceramic sand mortar and the inner wall of the composite steel pipe prepared in this comparative example was 1.38 MPa; the 28-day compressive strength of the silica fume-basalt fiber synergistic modified ceramic sand mortar was 14.8 MPa, and the flexural strength was 4.2 MPa. The axial compressive strength of the composite steel pipe was 46.3% higher than that of the pure thin-walled steel pipe, its bending stiffness was 22.1% higher, its bending load capacity was 47.8% higher, and its axial compressive stiffness was 46.5% higher. During the grouting process, the mortar exhibited good fluidity and smooth venting; however, post-cut inspection revealed the presence of some minor pore defects inside the steel pipe.

[0042] Comparative Example 3 This comparative example provides a mortar-composite steel pipe for photovoltaic brackets. The difference from Example 1 is that no water-retaining thickener and defoamer are added to the silica fume-basalt fiber synergistic modified ceramic sand mortar, but modified nano magnesium oxide (0.5 parts) is added. The remaining components and proportions are the same as in Example 1. The manufacturing process is the same as in Example 1.

[0043] Testing revealed that the bond strength between the silica fume-basalt fiber synergistic modified ceramic sand mortar and the inner wall of the composite steel pipe prepared in this comparative example was 1.42 MPa; the 28-day compressive strength of the silica fume-basalt fiber synergistic modified ceramic sand mortar was 15.2 MPa, and the flexural strength was 4.5 MPa. The axial compressive strength of the composite steel pipe was 47.8% higher than that of the pure thin-walled steel pipe, its bending stiffness was 23.5% higher, its bending load capacity was 49.2% higher, and its axial compressive stiffness was 48.0% higher. Slight segregation of the mortar was observed during the grouting process, and a large number of air bubbles escaped from the vent holes.

[0044] Comparative Example 4 This comparative example provides a mortar-composite steel pipe for photovoltaic brackets. The difference from Example 1 is that the silica fume-basalt fiber synergistic modified ceramic sand mortar does not contain water-retaining thickeners and modified nano-magnesium oxide, but it does contain defoamer (0.15 parts). The remaining components and proportions are the same as in Example 1. The manufacturing process is the same as in Example 1.

[0045] Testing revealed that the bond strength between the silica fume-basalt fiber synergistic modified ceramic sand mortar and the inner wall of the composite steel pipe prepared in this comparative example was 1.30 MPa; the 28-day compressive strength of the silica fume-basalt fiber synergistic modified ceramic sand mortar was 14.5 MPa, and the flexural strength was 4.0 MPa. The axial compressive strength of the composite steel pipe was 44.2% higher than that of the pure thin-walled steel pipe, its bending stiffness was 20.5% higher, its bending load capacity was 45.3% higher, and its axial compressive stiffness was 44.8% higher. Air venting was smooth during the grouting process, and post-cut inspection revealed no obvious porosity defects inside the steel pipe, but the interfacial bonding between the mortar and the inner wall of the steel pipe was slightly weak.

[0046] Table 1: Summary of Performance Indicators of Examples 1-3 and Comparative Examples 1-4

[0047] As shown in Table 1: 1. The bonding strength (1.62-1.72 MPa) of Examples 1-3 was significantly higher than that of Comparative Example 1 (1.25 MPa), Comparative Example 2 (1.38 MPa), Comparative Example 3 (1.42 MPa) and Comparative Example 4 (1.30 MPa), indicating that the synergistic effect of the water-retaining thickener, modified nano magnesium oxide and defoamer has a significant effect on improving the interfacial bonding performance between mortar and steel pipe.

[0048] 2. The flexural strength (4.6-5.8 MPa) of Examples 1-3 was higher than that of Comparative Examples 1-4 (3.8-4.5 MPa), indicating that the synergistic effect of the three additives significantly improved the toughness of the mortar.

[0049] 3. The axial compression bearing capacity improvement of Examples 1-3 (48.5%-57.3%) was higher than that of Comparative Examples 1-4 (42.6%-47.8%), and the bending stiffness improvement of Examples 1-3 (24.6%-29.1%) was higher than that of Comparative Examples 1-4 (19.8%-23.5%), indicating that the synergistic effect of the three additives has a significant contribution to the improvement of the overall mechanical properties of the composite steel pipe.

[0050] 4. The filling density of Examples 1-3 is better than that of Comparative Examples 1-3. Comparative Example 1 has a small number of honeycomb defects due to the lack of defoamer, while Comparative Examples 2 and 3 have individual pore defects due to the lack of some additives. This shows that the synergistic effect of defoamer, water-retaining thickener, and modified nano magnesium oxide effectively eliminates air bubbles in the grouting process and ensures the dense filling of mortar.

[0051] The above results indicate that the synergistic addition of water-retaining thickener, modified nano-magnesium oxide, and defoamer achieves multiple effects of "water retention and thickening to prevent segregation + nano-filling reinforcement + defoaming to eliminate defects," comprehensively improving the quality of composite steel pipes from three dimensions: injection performance, interfacial adhesion, and long-term stability. Its overall performance is significantly better than that of the scheme lacking any of the additives.

[0052] Theoretical calculation verification of the load-bearing capacity of composite steel pipe 1. Referring to the "Code for Design of Steel-Concrete Composite Structures" GB 50936-2014, and using the load-bearing calculation method for steel-concrete composite members, the load-bearing capacity of a composite steel pipe consisting of a D70×2.0mm thin-walled Q355 round steel pipe filled with M15 modified mortar was calculated. The calculation parameters are as follows: Round steel pipe outer diameter: D=70mm, wall thickness t=2.0mm, inner diameter d=66mm; Q355 steel yield strength: f y =355MPa, elastic modulus E s =2.06×10 5 MPa; M15 mortar compressive strength: f c =7.2MPa, elastic modulus E c =2.20×10 4 MMPa; Coefficients for round steel pipes: B=1.23, C=-0.021; Q355 steel k e =719.6; Steel pipe cross-sectional area: A s ≈427.26mm 2 Core concrete cross-sectional area: A c ≈3421.19mm 2 ; Gross cross-sectional area of ​​steel-concrete composite pipe: A sc ≈3848.45mm 2 Moment of inertia of steel pipe section: I s ≈247170.5mm 4 ; Moment of inertia of the core concrete section: I c ≈931400.3mm 4 Radius of gyration of empty steel pipe: i s ≈24.05mm; Calculated length of component: L0 = 1683.5 mm.

[0053] 2. Calculation of axial compressive bearing capacity of hollow circular steel pipe: Regular slenderness ratio: λn≈0.925, stability coefficient: φ=0.648, axial compressive stability bearing capacity: N0≈85.8kN, local stability check: diameter-to-thickness ratio 35<66.2.

[0054] 3. Calculation of composite round steel pipe filled with M15 mortar Hooping coefficient: ξ=5.0; Design value of axial compressive strength: f sc =(1.212+B*ξ+C*ξ 2 )f c ≈49.23MPa; Elastic modulus: E sc ≈4.605×10 4 MPa; Equivalent radius of gyration of composite steel pipe: i sc ≈20.91mm; Slenderness ratio of composite steel pipe: λ sc ≈80.51; Regular slenderness ratio: λ n ≈0.838; Stability coefficient: φ = 0.701; Axial compression stable bearing capacity: N≈132.8kN Local stability check: diameter-to-thickness ratio 35 < 89.4.

[0055] like Figure 2 As shown, the results of the finite element analysis (using ABAQUS software) are shown in Table 2-4.

[0056] Table 2: Comparison of Performance Indicators between Hollow Round Steel and Composite Round Steel Pipes

[0057] Table 3: Comparison of Load-Bearing Capacity Types of Hollow Round Steel Pipes and Composite Round Steel Pipes

[0058] Table 4: Comparison of Stiffness Types of Hollow Round Steel and Composite Round Steel Pipes

[0059] Both theoretical calculations and finite element analysis results show that the load-bearing capacity and stiffness of the composite steel pipe of the present invention are significantly improved compared with those of pure thin-walled steel pipe.

[0060] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A mortar-composite steel pipe for photovoltaic brackets, characterized in that, The mortar comprises a steel pipe and a silica fume-basalt fiber synergistic modified ceramic sand mortar injected inside the steel pipe. The silica fume-basalt fiber synergistic modified ceramic sand mortar, by weight, consists of the following components: 200-400 parts cement; 50-150 parts fly ash; 20-60 parts silica fume; 500-800 parts of graded ceramic sand; 2-10 parts of 6mm short-cut basalt fiber; 5-15 parts of micro-expansion agent; 5-15 parts of high-efficiency water-reducing agent; 5-20 parts of redispersible latex powder; 0.05-0.5 parts of water-retaining thickener; 0.2-1.0 parts of modified nano-magnesium oxide; Defoamer 0.05-0.5 parts; 150-300 parts water; The modified ceramic sand mortar has a water-cement ratio of 0.62-0.96, a wet density of 1200-1500 kg / m³, a flowability of ≥200 mm, and a bond strength to the inner wall of the steel pipe of ≥1.2 MPa.

2. The mortar-composite steel pipe for photovoltaic support according to claim 1, characterized in that, The silica fume-basalt fiber synergistic modified ceramic sand mortar, by weight, consists of the following components: 250-350 parts cement; 80-120 parts fly ash; 30-50 parts silica fume; Graded ceramic sand 600-750 parts; 4-8 parts of 6mm short-cut basalt fiber; 8-12 parts of micro-expansion agent; 8-12 parts of high-efficiency water-reducing agent; 10-15 parts of redispersible latex powder; 0.08-0.3 parts of water-retaining thickener; 0.3-0.7 parts of modified nano-magnesium oxide; Defoamer 0.08-0.3 parts; 180-250 parts water.

3. The mortar-composite steel pipe for photovoltaic brackets according to claim 1, characterized in that, The water-retaining and thickening agent is at least one of styrax, hydroxypropyl methylcellulose ether, or starch ether, and the viscosity of the water-retaining and thickening agent is ≥10000 mPa·s; the outer diameter of the modified nano magnesium oxide is 10-50 nm; the defoamer is an organosilicon defoamer or a polyether defoamer.

4. The mortar-composite steel pipe for photovoltaic support according to claim 1, characterized in that, The redispersible latex powder is an ethylene-vinyl acetate copolymer latex powder with a solid content ≥98%, a minimum film-forming temperature ≤5℃, and a glass transition temperature of -5-10℃; the silica fume-basalt fiber synergistic modified ceramic sand mortar has a 28-day compressive strength of 10-20MPa, a flexural strength ≥4.5MPa, and a bond strength with steel pipe ≥1.6MPa.

5. The mortar-composite steel pipe for photovoltaic support according to claim 1, characterized in that, The graded ceramic sand is a continuous gradation of 0.0-2.5mm, with a bulk density of 700-900kg / m³, a compressive strength ≥1.5MPa, a water absorption rate ≤10%, and a moisture content ≤3%. The silica fume has a SiO2 content ≥90%, a specific surface area ≥15000m² / kg, and a water requirement ratio ≤115%. The 6mm short-cut basalt fibers have a tensile strength ≥3000MPa and an elastic modulus ≥80GPa. The micro-expansion agent has a restricted expansion rate of ≥0.02% at 7d and ≤0.10% at 28d. The high-efficiency water-reducing agent is a retarded polycarboxylate water-reducing agent with a water reduction rate ≥20%.

6. The mortar-composite steel pipe for photovoltaic support according to claim 1, characterized in that, The steel pipe is made of Q235 or Q355 steel with a yield strength ≥235MPa, a wall thickness of 2.0-5.0mm, an outer diameter of 30-150mm, and a length of 1.0-5.0m; the surface of the steel pipe is provided with a hot-dip galvanized layer with a galvanized layer thickness ≥85μm.

7. The mortar-composite steel pipe for photovoltaic support according to claim 1, characterized in that, The steel pipe is a round or square pipe; both ends of the steel pipe are provided with sealing plugs, which are made of steel of the same material as the steel pipe and have the same thickness as the steel pipe wall thickness. One end of the steel pipe is provided with a 15-25mm grouting hole, and the other end is provided with a 5-8mm diameter venting hole; the silica fume-basalt fiber synergistic modified ceramic sand mortar is tightly bonded to the inner wall of the steel pipe without gaps, honeycomb, or voids.

8. The mortar-composite steel pipe for photovoltaic brackets according to claim 1, characterized in that, The composite steel pipe has a 40%-60% higher axial compressive strength than pure thin-walled steel pipe, a 20%-30% higher bending stiffness than pure thin-walled steel pipe, a 40%-60% higher bending load capacity than pure thin-walled steel pipe, and a 40%-60% higher axial compressive stiffness than pure thin-walled steel pipe.

9. A manufacturing process for a mortar-composite steel pipe for photovoltaic brackets as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Steel pipe pretreatment: Select Q235 or Q355 thin-walled steel pipes, remove rust, oil and impurities from the inner wall of the steel pipe, and use sandblasting to make the inner wall roughness reach Sa2.5 level; hot-dip galvanize the surface of the steel pipe, with a zinc layer thickness ≥85μm; weld and connect multiple steel pipes, with the total length controlled at 50-100 meters; weld sealing plugs at both ends of the steel pipe, and set a grouting hole at one end and an exhaust hole at the other end; S2. Preparation of silica fume-basalt fiber synergistic modified ceramic sand mortar: Weigh each component according to the proportion, dry the graded ceramic sand to a moisture content ≤3%, dissolve the high-efficiency water-reducing agent in all water to prepare an aqueous solution for later use; dry mix cement, fly ash, silica fume, micro-expansion agent, redispersible latex powder, water-retaining thickener, modified nano magnesium oxide, and defoamer evenly, then add the graded ceramic sand and 6mm short-cut basalt fiber and continue dry mixing to ensure that the fiber does not agglomerate; add the aqueous solution and wet mix for 2-3 minutes, let stand for 30 seconds and then test the flowability and bulk density until the design requirements are met; S3. Mortar injection: The silica fume-basalt fiber co-modified ceramic sand mortar prepared in S2 is injected into the pretreated thin-walled steel pipe by low-pressure pumping. It is slowly injected from the injection hole, and the air in the pipe is discharged by the vent hole. The injection is stopped when the mortar overflows from the vent hole and no more air bubbles emerge. The vent hole is then sealed. S4. Curing and Shaping: After the cast composite steel pipe has been cured to 50% of its design strength, it is cut according to the design requirements and the ends of the steel pipe are ground and trimmed; curing continues until the design strength is reached, and the production is completed after passing the test.

10. The manufacturing process according to claim 9, characterized in that, In S3, the low-pressure pump pressure is controlled at 0.2-0.5MPa, and the grouting speed is 0.5-1.0m³ / h. During the grouting process, the venting status of the vent hole is observed in real time. If mortar segregation or clumping occurs, the grouting is stopped immediately, the mortar is re-stirred, and then the process is continued. In S4, the composite steel pipe is protected from impact and vibration during the curing process. After curing, the bonding strength, bending stiffness and load-bearing capacity of the composite steel pipe are tested. After passing the test, it is used for photovoltaic bracket assembly.